2010
DOI: 10.1002/jso.21648
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of E‐Selectin S128R gene polymorphism in pancreatic cancer

Abstract: E-selectin S128R "C" allele may confer an increased susceptibility to pancreatic cancer development, while its carriage status does not appear to be related to the aggressive features of this malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Although the association wasnotstatisticallysupportedforthegenotypes,wefounda higherrepresentationoftheSer/ArgandArg/Arggenotypes inbreastcancerpatientscomparedwiththehealthyindividuals, which is in agreement with other studies on pancreatic [20]andcolorectal [18,19]cancer.Sincethisistheonlypaper thatevaluatestheE-selectinpolymorphisminbreastcancer, we compared the allelic and genotypic distribution of our healthycontrolswiththoserecruitedforpancreatic [20]and colorectalcancer [18,19]studies.AmongtheFrenchhealthy subjects, Hebbar et al [19] noted that the Ser/Ser genotype waspresentin85.5%,theArgallelegenotype(Ser/Arg+Arg/ Arg)in14.5%,andtheArgallelein7.9%oftheindividuals. Alessandroetal.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Although the association wasnotstatisticallysupportedforthegenotypes,wefounda higherrepresentationoftheSer/ArgandArg/Arggenotypes inbreastcancerpatientscomparedwiththehealthyindividuals, which is in agreement with other studies on pancreatic [20]andcolorectal [18,19]cancer.Sincethisistheonlypaper thatevaluatestheE-selectinpolymorphisminbreastcancer, we compared the allelic and genotypic distribution of our healthycontrolswiththoserecruitedforpancreatic [20]and colorectalcancer [18,19]studies.AmongtheFrenchhealthy subjects, Hebbar et al [19] noted that the Ser/Ser genotype waspresentin85.5%,theArgallelegenotype(Ser/Arg+Arg/ Arg)in14.5%,andtheArgallelein7.9%oftheindividuals. Alessandroetal.…”
Section: Discussionsupporting
confidence: 90%
“…[18]reportedthat90%ofCaucasianswere Ser/Ser homozygotes, 10% were carriers of the Arg allele genotype,and5%werecarriersoftheArgallele.Inanother study,Panoussopoulosetal. [20]foundthat63.75and36.25% of the Greek healthy subjects were carriers of Ser/Ser and Argallelegenotypes,respectively,and22.8%werecarriersof…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Of these, 150 publications were excluded because of case reports, or reviews, or non-relevance research, or duplicate data, or incomplete date. Finally, eight studies were included in this metaanalysis, with a total of 1,675 cancer cases and 2,285 controls (Alessandro et al, 2007;Bai, 2009;Hebbar et al, 2009;Panoussopoulos et al, 2010;Naidu et al, 2011;Xia et al, 2012;Kontogianni et al, 2013;Liarmakopoulos et al, 2013). A flow diagram schematized the process of selecting and excluding articles with specific reasons was shown in Figure 1, and the main characteristics of eligible studies were shown in Table 1.…”
Section: Studies Selection and Characteristicsmentioning
confidence: 99%